The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsaem.1c01692
|View full text |Cite
|
Sign up to set email alerts
|

Improved OER Performance on the Carbon Composite Electrode through Tailored Wettability

Abstract: This work reports an improved oxygen evolution reaction (OER) activity on a carbon–polymer composite-based tailored electrode, the plastic chip electrode (PCE). Glassy carbon electrodes (GCEs) have been often used as an electrode platform in water-splitting experiments, mostly due to their suitable physicochemical properties and omnipresence. However, the OER kinetics on carbon electrodes are reported to be limited. Passivation of the electrode surface due to slow scavenging of the formed oxygen is presumably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…LSV was performed in a typical three-electrode system in the alkaline electrolyte (1 M KOH) at a scan rate of 5 mVs –1 . All of the experiments were performed using PCE as the electrode support due to negligible activity toward the OER and it resolves the bubble-related issue in the catalyst as it has hydrophobic nature that repels the generated oxygen gas bubbles . To activate the electrocatalyst-modified electrode, CV cycles were first performed at a scan rate of 500 mVs -1 until a uniform CV curve was attained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…LSV was performed in a typical three-electrode system in the alkaline electrolyte (1 M KOH) at a scan rate of 5 mVs –1 . All of the experiments were performed using PCE as the electrode support due to negligible activity toward the OER and it resolves the bubble-related issue in the catalyst as it has hydrophobic nature that repels the generated oxygen gas bubbles . To activate the electrocatalyst-modified electrode, CV cycles were first performed at a scan rate of 500 mVs -1 until a uniform CV curve was attained.…”
Section: Resultsmentioning
confidence: 99%
“…PCE was fabricated using the previous reported method . A mixture of 10% (w/v) PMMA and graphite in chloroform in the ratio of 60:40 (w/v) was taken.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current strategies for enhancing PEC-WS performance are mainly through improving the light absorption efficiency, carrier separation efficiency, and transfer efficiency. Numerous endeavors have demonstrated that surface engineering can effectively promote carrier separation and transfer by reducing surface recombination, commonly including oxygen evolution catalysts (e.g., FeOOH, NiOOH, Co–Pi), surface passivation layer (e.g., Al 2 O 3 , TiO 2 ), and dual-absorber configuration (e.g., Si/α-Fe 2 O 3 , BiVO 4 /TiO 2 ). For instance, Wang et al prepared the BiVO 4 photoanodes with surface catalyst modulation and showed that a mixture of NiOOH/NiO/Ni as oxygen evolution catalysts could remarkably improve the charge transfer efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The plastic chip electrode (PCE) is one such polymer composite electrode developed by our group. [12] Having bulk conductivity coupled with self-standing flat and thin morphology, these electrodes helped in improving the efficiencies in sensing [13][14][15] electrocatalysis, [16] and electrometallurgy [17] applications. The PCE is fabricated by mixing its components in the solution phase followed by evaporation of the solvent under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%